Low‐grade epilepsy‐associated tumour management with or without presurgical evaluation: a multicentre, retrospective, observational study of postsurgical epilepsy outcome. Issue 5 (24th November 2020) - Ristić, Aleksandar J.; Mindruta, Ioana; Dimova, Petia; Kelemen, Anna; Grujičić, Danica; Ilić, Rosanda; Baščarević, Vladimir; Stoica, Sergiu; Pavel, Sebastia; Minkin, Krasimir; Gabrovski, Kaloyan; Raičević, Savo; et al.
Abstract: Aims Low‐grade epilepsy‐associated neuroepithelial tumours (LEATs) encompass the broad spectrum of tumours associated with epilepsy. Since the postsurgical seizure outcome in LEATs is favourable, it is speculated that epileptological presurgical evaluation (EPE) might not be required for patients with LEATs. Methods A multicentre study involving referring epilepsy and neurosurgery centres was performed, aimed at evaluating postsurgical epilepsy outcome in patients with LEATs, with and without EPE, including long‐term video‐EEG monitoring (vEEGM). In total, 149 surgically treated patients were enrolled (age: 31±14 years; age at surgery: 26.4±13.1 years; males; 55.7%) with histopathological confirmation of LEATs and follow‐up of more than six months. All patients had undergone standard assessment: clinical, routine EEG and brain MRI. In addition to vEEGM, EPE included other additional investigations. Epileptologists did not assess patients treated in neurosurgical centres. The EPE was performed in 51% of patients. Results Histopathological diagnosis revealed ganglioglioma in 43.6%, DNET in 32.9%, pilocytic astrocytoma in 17.4%, and others in 6.1% of patients. The majority of patients were seizure‐free (ILAE epilepsy surgery outcome Class 1; 71.1%). The median follow‐up period was 36 months. Patients who were rendered seizure‐free were younger (mean age: 24.2±12.2) than those who were not seizure‐free (31.8±14.0) ( p =0.001). No difference was identified between evaluated and non‐evaluated patients with respect to seizure freedom ( p =0.45). EPE patients had a longer epilepsy duration (median: 10 years) and a higher proportion of drug resistance (73.6%) compared to non‐evaluated patients (median: two years; 26.4%) ( p <0.001). Based on a significant difference in major clinical variables, that may well affect postoperative results, the similar postsurgical seizure outcome in groups with and without EPE observed in our study should be considered with caution, and conclusions as to whether there is value in formal presurgical evaluation in LEAT patients cannot be drawn. Conclusions Our data strongly encourage the clear need for continued discussion around such patients at epilepsy management conferences.